Significant association of hyperandrogenism and insulin resistance with the epigenetic alterations in PPARG1 gene in granulosa cells of PCOS females - Zahra Dashti; Vahid Razban; Jafar Fallahi; Mohammad ebrahim Parsanezhad; Shayesteh Mehdinejadiani; Nasrin Ghasemi (Egyptian Journal of Medical Human Genetics)
Abstract Background Polycystic ovary syndrome (PCOS) is one of the most prevalent endocrine and metabolic disorders, affecting approximately 15% of females. This syndrome is characterized by its remarkable heterogeneity, and epigenetic factors may contribute to its development. Since the PPARG gene is crucial for lipid and glucose metabolism, this study investigated the correlation between hyperinsulinemia, hyperandrogenism, and PPARG1 methylation in granulosa cells of polycystic ovary syndrome patients. Methods Follicular fluid was collected from 30 healthy control subjects, 25 patients with PCOS, and further subdivided into groups of 20 patients with PCOS exhibiting hyperandrogenism and insulin resistance, respectively. Granulosa cells were isolated from the follicular fluid. Subsequently, RNA and DNA were extracted, and bisulfite conversion was performed to analyze DNA methylation. The methylation status of the PPARG1 gene was assessed using MS-PCR, and qRT-PCR was employed to quantify PPARG1 mRNA expression. Results Analysis of the data revealed significant differences in PPARG1 gene methylation among the four patient groups. Notably, the PPARG1 gene promoter exhibited hypermethylation in both the PCOS-IR and PCOS-HA groups. This hypermethylation was associated with subsequent downregulation of PPARG1 gene expression compared to the control group (p < 0.05). Conclusion Our findings provide compelling evidence for the epigenetic regulation of PPARG1 in PCOS. PPARG1 promoter hypermethylation was observed specifically in PCOS patients with insulin resistance (IR) and hyperandrogenism (HA), suggesting a potential role for DNA methylation in the downregulation of PPARG1 expression in these subgroups. This link between PPARG1 methylation and gene expression required further investigation to elucidate its functional significance in the pathogenesis of PCOS.